RANCANG BANGUN SISTEM INFORMASI LOWONGAN PEKERJAAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS REACT NATIVE - Kaloka, Indra Arsy; Mochammad Sidqon (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
TalentVibes is a recruitment services company serving various industries. Currently, the TalentVibes recruitment system is web-based and faces major issues with responsiveness on mobile devices, causing inconvenience for visitors and difficulties in user management. To enhance its services, TalentVibes has designed and developed a mobile-based recruitment information system using React Native. This system facilitates the recruitment process and allows easier access for applicants. The application employs the Simple Additive Weighting (SAW) method to evaluate and select candidates based on predetermined criteria. The SAW method enables multi-criteria comparison by assigning weights to each criterion and then summing the total scores to choose the best candidate. With React Native, the application can run on both Android and iOS platforms. The Waterfall development method is used to ensure a linear and structured system development according to user requirements. Test results indicate that the system can improve the efficiency and accuracy of the job vacancy search and selection process.